2017
DOI: 10.22325/fes/res.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Las expectativas parentales no explican el rendimiento escolar

Abstract: RESUMENDesde la formulación inicial del "modelo Wisconsin" numerosos autores han postulado las expectativas parentales como un determinante principal de las diferencias de éxito escolar por origen social. Unas expectativas mayores incrementarían el apoyo escolar parental y el autoconcepto y las expectativas filiales. Otros autores critican esta teoría, afirmando que las expectativas dependen del éxito escolar. Contrastamos ambas teorías con los datos de la Encuesta Social 2010, que permite comparar dos cohorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
2
0
6
Order By: Relevance
“…We can say then that high expectations cause high academic performance. However, research in the Spanish case about that causal relationship is more prone to affirm the opposite: high generalized initial levels of ambition are downgraded as a response to poor demonstrations of academic ability (Criado & Bueno, 2017;Elias & Daza, 2019). Even more, it has been argued that generalized unrealistically high expectations about higher education may lead to undesirable results, such as a shared consideration of previous preparation as irrelevant to attend higher education and the consequent reduction of effort in the preparatory levels for university (Rosenbaum, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We can say then that high expectations cause high academic performance. However, research in the Spanish case about that causal relationship is more prone to affirm the opposite: high generalized initial levels of ambition are downgraded as a response to poor demonstrations of academic ability (Criado & Bueno, 2017;Elias & Daza, 2019). Even more, it has been argued that generalized unrealistically high expectations about higher education may lead to undesirable results, such as a shared consideration of previous preparation as irrelevant to attend higher education and the consequent reduction of effort in the preparatory levels for university (Rosenbaum, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Other works have shown a high degree of adaptability of academic expectations to educational performance. For instance, Criado and Bueno (2017) studied two cohorts of Spanish students in 2010 whose parents were asked about their educational expectations about their children. The authors observed that expectations were far more related to academic results at 16 years of age than at 12 because low-performers' parents lowered their initial expectations.…”
mentioning
confidence: 99%
“…En este punto se puede afirmar, tal y como apuntan otros autores (Capsada, 2014;Carabaña, 2015;Martín Criado y Gómez, 2017) que las experiencias en el ámbito educativo -con las notas como variable más visible-son un fuerte configurador de las expectativas de los jóvenes. Pero cabe decir que no funciona por igual en todos los colectivos, los jóvenes de familias con niveles educativos obligatorios y los de niveles educativos universitarios se ven menos influidos por las notas.…”
Section: Discussionunclassified
“…Este fenómeno conlleva, en palabras de Vaquero (2005Vaquero ( , p. 1443) "una pérdida importante de oportunidades para aumentar el nivel educativo y, al mismo tiempo, un desaprovechamiento de recursos públicos". Además, parte de las expectativas que se crean en torno al éxito o fracaso escolar tienen que ver en la familia, donde el desajuste entre los resultados y el éxito en los estudios se debe al nivel educativo de los padres, a las expectativas que se crean en torno a los jóvenes y el apoyo y la socialización dentro del entorno familiar (Martín Criado & Gómez, 2016;Martínez García, 2017).Para Tarabini y Curran, la importancia de la posición social de la familia es relevante y está relacionada con el hecho de continuar la formación o tener el riesgo de abandonarla:…”
Section: El Origen Del Concepto Ni-niunclassified